Legal Analysis of Corruption Crimes Extending Credit to Banks (Case Study: Tipikor Court Decisions at the Medan District Court No. 79, 80, and 81/Pid.Sus.K/2012/PN.Mdn., date 29/04/2013) (Mahadi: Indonesia Journal of Law, 2023)
In this study, the corruption case focuses on the regulation of credit distribution at state-owned banks with the legal entity of a Perseroan Terbatas (PT). The bank appointed was Bank BNI '46 related to the fictitious credit case An. Boy Hermansyah (BY) who until now has not been tried until now, while the associated officials of Bank BNI '46 have been tried and have received a court decision with permanent legal force. In fact, some of the defendants from Bank BNI '46 committed suicide, due to severe depression, because they were about to be detained. The case stems from the existence of credit disbursement in 2009, amounting to Rp. 129 billion made by a businessman from Aceh, Boy Hermansyah. The defendant in this case, such as Defendant D.A., is the Former Leader of the BNI '46 Business Marketing Group Pemuda Medan-Branch, Defendant R.D., as the Former Leader of the BNI '46 Sentra Kredit Menengah (SKM) and Defendant T.I., as Former Relationship BNI '46 SKM Pemuda Medan. The credit intended for the plantation business was not according to its designation; the assets that were pledged as collateral were also problematic. The disbursed funds are not used for business activities as stated. In the calculations, it was later discovered that the State suffered a loss of Rp. 117.5 billion and the public prosecutor assessed the involvement of the three defendants in the fictitious credit case. The problems, are: disbursement of credit that gives rise to criminal acts of corruption in state-owned bank PT; and the distribution of credit that led to criminal acts of corruption at Bank BNI'46 Pemuda Medan Branch. This study aims to analyze corruption crimes against the fictitious credit case of Bank BNI '46 Pemuda Medan-Branch. This type of research is normative research, with the nature of descriptive analysis research. The court's decision was obtained from the Registrar of the Corruption Court at the Medan District Court. The results of the study show that: 1) Credit disbursement that causes corruption at Bank BNI'46 Pemuda Medan Branch, the most important thing is that it must meet the element of "against the law in a formal sense", such as as stipulated in the laws and regulations in the banking sector, such as the application of the prudential banking principle. as mandated by Article 2 of the Banking Law. Only then is it associated with criminal acts of corruption as referred to in Article 2 paragraph (1) and Article 3, or even Article 5 and Article 12A of the Anti-Corruption Law, so that the distribution of credit can be categorized as a criminal act of corruption; and 2) Medan District Court Corruption Decisions No. 79, 80, and 81/Pid.Sus.K/2012/PN.Mdn., dated 29 April 2013 which has permanent legal force (inkracht) is not a criminal act of corruption, but only a case of bad credit at PT. Bank BNI'46 Pemuda Medan Branch with its customer PT. BDL.